P1. 15-15 Real-world Experience with Afatinib after Failure of First-Generation Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitor - Chai, Chee Shee; Ho, G.; Liam, Chong Kin; A, Binti Alip; Pang, Y. (Elsevier, 2018)
Background: Afatinib, a second-generation epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) is the recommended first-line treatment for patients with advanced non-small cell lung cancer harbouring sensitizing EGFR mutations. The role of afatinib after failure of first-generation EGFR-TKIs is controversial.